Fundamentals of English traditional syntax - Trần, Hữu Mạnh (Đại học Quốc gia Hà Nội, 2008)
Based on "A Grammar of Contemporary English" by Quirk R. et al., and "A University Grammar of English" by Quirk R. & Greenbaum S.